Opinion paper: scientific, philosophical and legal consideration of doping in sports - Negro, M.; Marzullo, N.; Caso, F.; Calanni, L.; D`Antona, G. (European Journal of Applied Physiology, 2018)
The term doping is generally used to indicate practices based on the use of performance-enhancing drugs (PEDs) or the abuse of medical therapies. Mostly analysed by doctors and officials, doping nevertheless also requires a philosophical consideration to avoid being simplistically portrayed as an isolated practice. To do this, we need to pay attention to the contradictions and paradoxes in the modern approach to doping in sport. In this context, doping is not only relevant to the health of an individual involved in the violation of World Anti-Doping Agency (WADA) criteria, but it actually represents a double-edged phenomenon containing ethical and legal points of view. Several philosophical items affect the ethics of doping. While, indeed, through a deontological vision it is easy to morally condemn an athlete who takes the decision to turn to doping, the same condemnation becomes difficult when the practice of doping is compared with the strong social demand of winners in every field of life. This point must be considered to prevent doping from becoming accepted as a daily practice to excel at all costs and regarded not only as normal but as a necessity for those participating in sport at both an amateur and professional level. Furthermore, a complete discussion on doping has to consider not only the philosophy of performance-enhancing drug abuse, but also the widespread practice of an inappropriate and excessive intake of certain dietary supplements with the unique and obsessive purpose (similar to doping) of increasing physical or mental performance. Based on the above, the aim of this paper is to provide a critical opinion of the doping problem and its related practices and analyze possible solutions considering issues that go beyond the impact of doping on health and reflect on whether it is right or not that an athlete does all he can to improve his performance.